Maternal Diet and the Serum Metabolome in Pregnancy: Robust Dietary Biomarkers Generalizable to a Multiethnic Birth Cohort. Issue 10 (2nd September 2020) - de Souza, Russell J; Shanmuganathan, Meera; Lamri, Amel; Atkinson, Stephanie A; Becker, Allan; Desai, Dipika; Gupta, Milan; Mandhane, Piush J; Moraes, Theo J; Morrison, Katherine M; Subbarao, Padmaja; Teo, Koon K; et al.
ABSTRACT: Background: Advances in metabolomics are anticipated to decipher associations between dietary exposures and health. Replication biomarker studies in different populations are critical to demonstrate generalizability. Objectives: To identify and validate robust serum metabolites associated with diet quality and specific foods in a multiethnic cohort of pregnant women. Design: In this cross-sectional analysis of 3 multiethnic Canadian birth cohorts, we collected semiquantitative FFQ and serum data from 900 women at the second trimester of pregnancy. We calculated a diet quality score (DQS), defined as daily servings of "healthy" minus "unhealthy" foods. Serum metabolomics was performed by multisegment injection-capillary electrophoresis-mass spectrometry, and specific serum metabolites associated with maternal DQSs were identified. We combined the results across all 3 cohorts using meta-analysis to classify robust dietary biomarkers ( r > ± 0.1; P < 0.05). Results: Diet quality was higher in the South Asian birth cohort (mean DQS = 7.1) than the 2 white Caucasian birth cohorts (mean DQS <3.2). Sixty-six metabolites were detected with high frequency (>75%) and adequate precision (CV <30%), and 47 were common to all cohorts. Hippuric acid was positively associated with healthy diet score in all cohorts, and with the overall DQS only in the primarily white Caucasian cohorts. We observed robust correlations between: 1 ) proline betaine—citrus foods; 2 ) 3-methylhistidine—red meat, chicken, and eggs; 3 ) hippuric acid—fruits and vegetables; 4 ) trimethylamine N -oxide (TMAO)—seafood, meat, and eggs; and 5 ) tryptophan betaine—nuts/legumes. Conclusions: Specific serum metabolites reflect intake of citrus fruit/juice, vegetables, animal foods, and nuts/legumes in pregnant women independent of ethnicity, fasting status, and delays to storage across multiple collection centers. Robust biomarkers of overall diet quality varied by cohort. Proline betaine, 3-methylhistidine, hippuric acid, TMAO, and tryptophan betaine were robust dietary biomarkers for investigations of maternal nutrition in diverse populations. Abstract : Study identifies robust dietary biomarkers of dietary patterns and foods in pregnant women.